Argentinean Experience in Highways Led Lighting - Ixtaina, Pablo Ruben (2017)
The impact of led luminaries on road lighting has modified traditional design patterns. The technological change proposes an installation with a higher prime cost and less energy consumption. On the one hand, the price ratio between led luminary and traditional luminary is at least 3:1. On the other, the led better energetic efficiency could allow keeping proper illumination levels with less installed power. In this frame, since mid 2013, the road concessionaires of highways which constitute the Access Network to Buenos Aires city (Argentina), together with Urban Highways of the mentioned city, began a restructuring process of their lighting systems to led technology. Framed in a review of efficiency concepts and energetic classification for road lighting installations, the work presents the main results of the previous evaluation tests and of the reconverted installations, which can be considered as the first led applications at large scale on road lighting of the region.